Peningkatan Kemampuan Analisis Pesan Puisi melalui Model Pembelaran Inquiry Learning Terbimbing pada Siswa Kelas XI IPS 5 SMAN 1 Asembagus Situbondo Tahun Pelajaran 2018/2019 - Sahri, Sahri (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2023)
This study uses classroom action research. The population in this study were all students of class XI IPS 5 in the fourth (even) semester of the 2018/2019 academic year, totaling 31. Thus, this research is classified as populative research. There are four stages in the implementation of actions in each cycle, namely (i) action planning, (ii) action implementation, and (iii) action observation, and (iv) action reflection. This classroom action research was conducted in two cycles. Before being given action, it turned out that the ability to analyze the poet's message in the poetry of class XI IPS 5 semester four (even) for the 2018/2019 academic year was very disappointing. As many as 31 students did not complete KKM 75. However, after the teacher changing the learning model using guided inquiry learning in cycle I, the ability to analyze the poet's message in poetry has increased tremendously normal. Of the 31 students, 30 students (97%) were declared to have reached KKM 75. There was only one student (3%) who was declared incomplete. In cycle II, the ability of class XI IPS 5 students in terms of analyzing the poet's message in poetry also experienced a remarkable increase. Of the 31 students, 31 students (100%) were declared complete with KKM 75. In addition, the scores obtained by each student also experienced a very significant increase.